2021
DOI: 10.1186/s40494-021-00525-0
|View full text |Cite
|
Sign up to set email alerts
|

The cultural and heritage tourist, SEM analysis: the case of The Citadel of the Catholic King

Abstract: This study researches the loyalty of travelers to destinations which include material cultural heritage. It analyzes the loyalty of visitors to a destination with cultural heritage sites in order to provide results which can be used to improve the management of the destination. This research used Warp-PLS 7.0 software with a structural equations model to evaluate the 8 proposed and validated hypotheses. A questionnaire was given to a sample of 499 tourists who visited The Citadel of the Catholic King in Córdob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 98 publications
1
8
0
5
Order By: Relevance
“…This implies that the least number of participants already contented exploring Ilocos Sur on their third visit. Returning tourists and visitors talk about their travel and experiences with loved ones and acquaintances and coworkers (Hernández-Rojas et al, 2021). The findings of Chen and Rahman (2018), show that tourists' inclinations to return to and suggest a cultural site are positively influenced by their pleasant tourism experiences.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This implies that the least number of participants already contented exploring Ilocos Sur on their third visit. Returning tourists and visitors talk about their travel and experiences with loved ones and acquaintances and coworkers (Hernández-Rojas et al, 2021). The findings of Chen and Rahman (2018), show that tourists' inclinations to return to and suggest a cultural site are positively influenced by their pleasant tourism experiences.…”
Section: Resultsmentioning
confidence: 98%
“…When planning a trip, the tourist compares his or her expectations of the destination's cultural and historic quality with what he or she actually experiences when they arrive at the destination. They do this by talking to locals, staying in hotels, visiting monuments, and taking in the sights of the heritage city as a whole (Hernández-Rojas et al, 2021). The findings of Sánchez-Fernández et al (2020) concluded that exceeding expectations is crucial for customer preference.…”
Section: Tourists' Expectation To Heritage Sitesmentioning
confidence: 99%
“…According to destination theory, cultural heritage travel motivation partakes in a unique experience in the visit of tourists, experience in the destination (Su, Nguyen, et al, 2020). Furthermore, several studies have found that higher levels of satisfaction with a particular destination do not lead to an increase in the number of people returning because repeat visits cannot guarantee the destination's tourist demand (Zhu et al, 2017); and promote the destination as part of their historical experience (Hernandez-Rojas et al, 2021;Sato, et al, 2018). In this context, satisfied cultural heritage tourists are motivated to return to the destination (Nguyen, et al, 2021;Le, et Tourist satisfaction, perceived value, and behavioral intention to revisit cultural heritage tourists al., 2020), and perceived value for tourist motivation, involvement, and purchase intention (Liu, 2021;Prebensen, et al, 2012), and the destination should be revisited for tourism development (Liu, 2021;Prebensen, Woo, et al, 2012;Teo, Khan, et al, 2014;Bandala, 2017).…”
Section: Tourist Satisfaction Perceived Value and Behavioral Intentio...mentioning
confidence: 99%
“…En la preparación y visualización del mapa de expresiones comunes se debe distinguir: La identificación de las palabras clave, posterior se usó un filtro de frases nominales, a los cuales se les denomina términos (Hofmann y Chisholm, 2015;Ferasso et al, 2020;Hernández-Rojas et al, 2021).…”
Section: Metodologíaunclassified